2005
DOI: 10.1016/j.femsle.2005.05.040
|View full text |Cite
|
Sign up to set email alerts
|

Fine affinity discrimination by normalized fluorescence activated cell sorting in staphylococcal surface display

Abstract: We have investigated a staphylococcal surface display system for its potential future use as a protein library display system in combinatorial biochemistry. Efficient affinity-based selections require a system capable of fine affinity discrimination of closely related binders to minimize the loss of potentially improved variants. In this study, a significant breakthrough was achieved to avoid biases due to potential cell-to-cell variations in surface expression levels, since it was found that a generic protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
54
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 49 publications
0
54
0
1
Order By: Relevance
“…It has previously been demonstrated that staphylococcal cell surface display in combination with fluorescenceactivated cell sorting (FACS) is well suited for combinatorial affinity maturation efforts, since it allows for high precision affinity discrimination between binders [35][36][37][38]. Recently, the method was used for affinity maturation of a HER3-specific Affibody, and generated binders with picomolar affinities [39].…”
Section: A Truncated and Dimeric Format Of An Affibody Library On Bacmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been demonstrated that staphylococcal cell surface display in combination with fluorescenceactivated cell sorting (FACS) is well suited for combinatorial affinity maturation efforts, since it allows for high precision affinity discrimination between binders [35][36][37][38]. Recently, the method was used for affinity maturation of a HER3-specific Affibody, and generated binders with picomolar affinities [39].…”
Section: A Truncated and Dimeric Format Of An Affibody Library On Bacmentioning
confidence: 99%
“…It has been shown that there is a correlation between the affinity of peripherally-administered Ab-specific agents and the efflux of Ab from the brain to the serum [29]. As levels of Ab peptides in the blood are low (subnanomolar) [30][31][32][33][34], it is probably critical to use capturing-agents of high affinity for such applications.It has previously been demonstrated that staphylococcal cell surface display in combination with fluorescenceactivated cell sorting (FACS) is well suited for combinatorial affinity maturation efforts, since it allows for high precision affinity discrimination between binders [35][36][37][38]. Recently, the method was used for affinity maturation of a HER3-specific Affibody, and generated binders with picomolar affinities [39].…”
mentioning
confidence: 99%
“…We have previously described a system for display of proteins and peptides on the cell surface of the gram-positive bacterium Staphylococcus carnosus (17, 36-39, 45, 51-55). The staphylococcal display system has recently been improved for protein engineering purposes (20), and optimization of the electroporation protocol has increased the transformation frequency to approximately 10 6 transformants per transformation (19), enabling the construction of large displayed combinatorial protein libraries. A 58-amino-acid, three-helical-bundle protein, derived from staphylococcal protein A (24), has been used as a protein engineering scaffold, and the randomized and selected affinity proteins are denoted affibody molecules (12,26,27,30).…”
mentioning
confidence: 99%
“…In order to do this for the novel staphylococcal cell surface display method, we have determined the equilibrium dissociation constants (K D ) of three related affibody molecules (Z wt , Z N28A , and Z K35A ) (20) with affinity for human immunoglobulin G (IgG) by cell display together with flow cytometry and by biosensor analysis. Furthermore, the K D and the dissociation rate constant (k off ) of an albumin binding domain (ABD wt ) (44) for human serum albumin (HSA) have been determined using both methods.…”
mentioning
confidence: 99%
“…ДНК, що кодує досліджуваний протеїн-антиген, ампліфікується за допомогою полімеразної ланцюгової реакції та фрагментується за допомогою ультразву-ку до розмірів у 50-150 нуклеотидів, після чого одержані фрагменти ДНК клонуються у бактеріальний вектор (разом із послідовністю, що кодує альбумінзв'язувальний протеїн), яким клітини Staphylococcus carnosus транс-формуються шляхом електропорації. Таким чином, фрагменти антигену є «зшитими» із альбумінзв'язувальним протеїном, що відіграє роль молекулярного спейсера між клітинною стінкою та досліджуваним пептидом, а та-кож є важливим для подальшого сортування клітин у проточній цитофлуорометрії [46,47]. Синтезовані та експресовані на поверхні S. carnosus пептиди на наступному етапі взаємодіють із міченими антитілами та людсь-…”
Section: рисunclassified